Virulence factors of Mycoplasma synoviae: Three genes influencing colonization, immunogenicity, and transmissibility - Klose, Sara M.; Omotainse, Oluwadamilola S.; Zare, Sahar; Vaz, Paola K.; Armat, Parisa; Shil, Pollob; Wawegama, Nadeeka; Kanci Condello, Anna; O'Rourke, Denise; Disint, Jillian F.; Andrews, Daniel M.; Underwood, Gregory J.; et al. (Frontiers in Microbiology, 2022)
Infections caused by Mycoplasma synoviae are major welfare and economic concerns in poultry industries worldwide. These infections cause chronic respiratory disease and/or synovitis in chickens and turkeys leading to reduced production and increased mortality rates. The live attenuated vaccine strain MS-H (Vaxsafe® MS), commonly used for protection against M. synoviae infection in many countries, contains 32 single nucleotide variations compared to its wildtype parent strain, 86079/7NS. Genomic analysis of vaccine strains reisolated from flocks following the administration of MS-H has identified reversions to the original 86079/7NS sequence in the obgE, oppF and gapdh genes. Here, three MS-H field reisolates containing the 86079/7NS genotype in obgE (AS2), obgE and oppF (AB1), and obgE, oppF and gapdh (TS4), as well as the vaccine MS-H and the parental strain 86079/7NS were experimentally inoculated to chickens. The strains were assessed for their ability to infect and elicit immune responses in the recipient chickens, as well as in naïve in-contact chickens. Despite the loss of temperature sensitivity phenotype and colonisation of the reisolates in the lower respiratory tract, there was no significant differences detected in the microscopic mucosal thickness of the middle or lower trachea of the inoculated chickens. Concurrent reversions in ObgE, OppF and GAPDH proteins were associated with higher gross air sac lesion scores and increased microscopic upper-tracheal mucosal thickness in chickens directly inoculated with the reisolates following intratracheal administration of a virulent strain of Infectious Bronchitis Virus (IBV). The gross air sac lesions of the chickens in-contact with those inoculated with reisolates were not significantly different to those of chickens in-contact with MS-H inoculated chickens, suggesting that horizontal transmission of the reisolates in the poultry flock will not lead to higher pathogenicity or clinical signs. These results suggest a significant role of GAPDH and/or cumulative effect of ObgE, OppF and GAPDH on M. synoviae pathogenicity. Future experiments will be required to investigate the effect of single mutations in gapdh or oppF gene on pathogenicity of M. synoviae.